Sport training day affects adolescent athletes` sleep schedules - Larson, A.; Street, J. H.; de Guia, R.; Capin, J. J. (Frontiers in Sports and Active Living, 2025)
Introduction: Sufficient sleep is integral to overall health whereas suboptimal sleep puts athletes at greater risk for injury, lengthens their recovery time, and decreases their performance. Our purpose was to compare sleep across training days (i.e., competition, practice, and rest) in adolescent athletes, specifically identifying differences between nights before and after training. Methods: Participants [n = 33 (14 male, 19 female), aged 15.6 ± 1.0 years] wore an activPAL accelerometer continuously for 14 consecutive days and completed a sleep log noting training day status (i.e., competition, practice, rest). Results: Athletes slept less on the day after competition compared to after practice and rest days [Sleep Duration (mean ± SD) after competition: 7.9 ± 1.6 h, after practice: 8.6 ± 0.8 h, after rest: 9.2 ± 1.4 h, interaction effect p < 0.001]. The time athletes went to bed tended to be later before and after rest days compared with competition and practice days [Time in Bed Start (hr:min, mean ± SD) before competition: 22:02 ± 0:58, after competition: 22:19 ± 1:03, before practice: 22:20 ± 0:49, after practice: 22:06 ± 0:40, before rest: 22:55 ± 1:09, after rest: 23:13 ± 0:58, p = 0.080]. Athletes woke up the latest on and after rest days (before competition: 6:52 ± 1:16, after competition: 6:11 ± 1:21, before practice: 6:59 ± 0:43, after practice: 6:43 ± 0:42, before rest: 7:35 ± 1:09, after rest: 8:26 ± 1:22, p < 0.001). Conclusion: In conclusion, athletes slept less the day after a competition compared with the day after a practice or rest day. While sleep start times did not differ by training day, athletes woke up later before and after rest days. Understanding factors influencing athletes` sleep may enable health care providers and coaches to help athletes stay healthy and optimize their performance.